2022
DOI: 10.1021/acs.joc.2c01157
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Halogenated Xanthones by a Divergent Coupling Strategy

Abstract: A versatile strategy to halogenated xanthones was developed that relies on a modular coupling of vanillin derivatives with a dibromoquinone. Depending on the reaction conditions, either the 6-or the 7-bromo heterocycles may be obtained in a divergent manner. These heterocycles may be readily further elaborated by sequential Sonogashira couplings, and the sequence may be successfully applied to substructures of the antibiotic lysolipin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As exemplarily shown for hydroquinone 11 b in Table 3, we found that demethylation at the C1 anisole limits the scope of the sulfuric acid promoted cyclization. Since this demethylation occurred irrespective of the employed temperature (entries 1–3), we argued that the high Brønstedt acidity of commonly used sulfuric acid is the cause [13,17] . Indeed, less acidic methanesulfonic acid completely suppressed this demethylation and gave xanthone 12 b in useful yield after four hours at elevated temperatures (59 %, entry 4–5).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…As exemplarily shown for hydroquinone 11 b in Table 3, we found that demethylation at the C1 anisole limits the scope of the sulfuric acid promoted cyclization. Since this demethylation occurred irrespective of the employed temperature (entries 1–3), we argued that the high Brønstedt acidity of commonly used sulfuric acid is the cause [13,17] . Indeed, less acidic methanesulfonic acid completely suppressed this demethylation and gave xanthone 12 b in useful yield after four hours at elevated temperatures (59 %, entry 4–5).…”
Section: Resultsmentioning
confidence: 93%
“…used sulfuric acid is the cause. [13,17] Indeed, less acidic methanesulfonic acid completely suppressed this demethylation and gave xanthone 12 b in useful yield after four hours at elevated temperatures (59 %, entry 4-5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations